Protein kinase A signaling and calcium ions are major players in PAF mediated toxicity against Aspergillus niger. Issue 11 (14th April 2015) - Binder, Ulrike; Benčina, Mojca; Fizil, Ádám; Batta, Gyula; Chhillar, Anil K.; Marx, Florentine
Abstract : The Penicillium chrysogenum antifungal protein PAF is toxic against potentially pathogenic Ascomycetes. We used the highly sensitive aequorin‐expressing model Aspergillus niger to identify a defined change in cytoplasmic free Ca 2+ dynamics in response to PAF. This Ca 2+ signature depended on an intact positively charged lysine‐rich PAF motif. By combining Ca 2+ measurements in A. niger mutants with deregulated cAMP/protein kinase A (PKA) signaling, we proved the interconnection of Ca 2+ perturbation and cAMP/PKA signaling in the mechanistic function of PAF. A deep understanding of the mode of action of PAF is an invaluable prerequisite for its future application as new antifungal drug. Abstract : Aspergillus niger is highly susceptible to the antifungal protein PAF. Ca 2+ and cAMP/PKA signalling are interconnected in response to PAF. PAF toxicity requires the activation of the cAMP/PkaA signaling cascade. PAF evokes a sustained increase in the [Ca 2+ ]c resting level. Only a functional PAF protein interferes with the fungal Ca 2+ homeostasis. PAF represents a promising molecule to develop new antifungal strategies.